FREQUENCY OF VITAMIN D INSUFFICIENCY IN GENERAL ADULT POPULATION IN PESHAWAR - Alam, Jan e; Jan, Amin; Khan, Bashir (Pakistan Journal of Physiology, 2016)
Background: Vitamin D insufficiency is now recognized as pandemic. The purpose of this study was to measure the frequency of vitamin D insufficiency among adult population in Peshawar, Pakistan. Methods: The study was conducted over a period of ten months in Peshawar Institute of Medical Sciences, Hayatabad, Peshawar, from Apr 2013 to Jan 2014. A total of 300 patients from both genders were included in study. Number of male and female cases was same and age group of both sexes was comparable. Age range was 15–70 years. Serum vitamin D and calcium levels were estimated using standard laboratory techniques. Results: Overall the number of vitamin D deficient cases was 65%. Among female patients, the vitamin D deficient cases were 76%. Low serum calcium was observed in 23% cases. Conclusion: Hypovitaminosis D was maximum in Pardah observing ladies, those belonging to low socioeconomic groups, and in postmenopausal ladies. Pak J Physiol 2016;12(1):13–4